Effect of Advanced Maternal Age on Pregnancy Outcomes and Vascular Function in the Rat. Issue 6 (June 2015) - Care, Alison S.; Bourque, Stephane L.; Morton, Jude S.; Hjartarson, Emma P.; Davidge, Sandra T.
Abstract : Advanced maternal age is becoming increasingly common in Western societies and is associated with increased maternal and fetal morbidity and mortality. We hypothesized that aging results in impaired vascular function in pregnancy because of increased vascular oxidative stress and resultant scavenging of nitric oxide in both uterine and systemic arteries, causing reduced uteroplacental perfusion and poor pregnancy outcomes. Using aged rats (9.5 months), we investigated the effect of a delayed first natural pregnancy on pregnancy outcomes and uterine and mesenteric artery function on gestational day 20. Delayed pregnancy in the rat reduced fertility by 46%, reduced litter size by 36%, caused fetal growth restriction, increased placental weight, and increased maternal systolic blood pressure (by 16 mm Hg). Uterine arteries from aged dams displayed reduced constriction to phenylephrine (young: 14.3±0.94 mN/mm versus aged: 11.4±0.5 mN/mm, P =0.02) and potassium chloride (124 mmol/L; young: 21.8±1.27 mN/mm versus aged: 14.2±1.7 mN/mm; P =0.01). Methacholine-induced vasodilation was similar in uterine arteries from young and aged dams. However, mesenteric arteries from aged dams had a greater nitric oxide and a reduced endothelial-derived hyperpolarization contribution to methacholine-mediated vasodilation compared with young dams. Both uterine and mesenteric arteries from aged dams had greater active myogenic responses, with area under the curve increased by 228% and 151%, in aged uterine and mesenteric arteries, respectively. These results demonstrate that vascular function is altered at an advanced maternal age and provides further insights into the risks of poor pregnancy outcomes observed in women who delay pregnancy. Abstract : Supplemental Digital Content is available in the text.